Qurban Sebagai Sarana Penguatan Nilai Nilai Kebersamaan dalam Masyarakat - Raka Noviandri; Elsita Insani; Latifha Umi Barakah; Sabila Ramadhani Lubis; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This research is motivated by the problems of life in modern society which increasingly tends to be individualistic and fragmented, for this reason, shared values ​​are becoming increasingly important to maintain. The aim of this research is to build unity between people who have different backgrounds, both in terms of social, economic and cultural aspects. The research method used is a descriptive qualitative approach, and the qualitative method was chosen because it allows researchers to understand social phenomena in more depth, with a focus on interactions between individuals, groups and communities in the context of sacrificial sacrifice. The research concludes that the results of this article are that the sacrificial service, with all the social processes that accompany it, has a very large role in building and strengthening shared values ​​in society, creating a more inclusive environment, and strengthening social relations between individuals with different backgrounds.